Characterization of the complete chloroplast genome of Hedysarum polybotrys var. alaschanicum (Fabaceae) and its phylogeny - Jia-Ning Cao; Chun-Rong Han; Yan-Ci Yang (Mitochondrial DNA. Part B. Resources, 2021)
Hedysarum polybotrys var. alaschanicum is an important medicinal plant and is widely used in traditional Chinese medicine. The complete chloroplast genome of H. polybotrys var. alaschanicum was assembled from Illumina pair-end sequence reads. The whole chloroplast genome is 122,933 bp in length and encodes a total of 110 genes, including 76 protein-coding genes, 30 tRNA genes and 4 rRNA genes. The overall GC content of the cp genome is 35.3%. A maximum likelihood (ML) phylogenetic analysis revealed that H. polybotrys var. alaschanicum was close to Hedysarum semenovii.